Conversions religieuses, conflits et continuités dans une communauté tlapanèque du Guerrero (Mexique) - Hébert, Martin (Anthropologica, 2022)
Despite the religious division at its centre, the Tlapaneque community of Barranca Tigre (Guerrero) did not experience the violence and expulsions that were common in other indigenous communities of Mexico in the throes of conflicts of a similar nature. This article seeks to examine some of the factors which contributed to the maintenance of social cohesion in this community since the first conversions to evangelical Protestantism in 1988. Though cross-cutting loyalties created by the contradiction between religious division and the need for economic cooperation within the community seem to have played an important part in the maintenance of this relative cohesion until 1992, the data indicate that one of the key elements in an understanding of this cohesion is the "overlapping continuity" (Fox 2004) in the attachment felt by both Catholics and Protestants to the imaginary social tradition of the community.